The evaluation of psychogenic non-epileptic seizures (PNES) cases with saline injection method in video-EEG monitorization unit - Bora, İbrahim; Demir, Aylin Bican; Ceylan, Dursun (Arquivos de Neuro-Psiquiatria, 2021)
Background: It has been reported that 10 to 30% of patients sent to epilepsy centers with a diagnosis of refractory epilepsy are diagnosed with psychogenic non-epileptic seizure (PNES). A wide variety of provocative methods are used to assist PNES diagnosis. Objective: To investigate the effect of seizure induction on the diagnosis and prognosis of PNES. Methods: We retrospectively examined 91 patients with PNES complaints in our video-EEG laboratory. Intravenous saline was administered to all patients for induction of seizures. Results: Saline injection was performed in 91 patients referred to our EEG lab with PNES initial diagnosis, 57 of whom were female and 34 male. Saline injection triggered an attack in 82 patients (90%). Conclusions: In this study we have concluded that provocative methods are practical, cheap and, most of all, effective for patient diagnosis. In clinical practice, explaining the diagnosis is the first and most important step of the treatment, and careful patient-doctor communication has a positive impact on patient prognosis.
Keywords: Seizures; Saline Solution; Electrocorticography